Hubungan Kadar High Density Lipoprotein (HDL) dengan Tekanan Darah pada Pasien Hipertensi - Tangkau, Victoria V. J.; Assa, Youla A.; Tiho, Murniati (e-CliniC, 2025)
Abstract: One of the indicators to identify a person's risk of hypertension is by measuring lipid profile. Measuring the high-density lipoprotein (HDL) cholesterol level in the lipid profile plays an important role in evaluating the risk of hypertension. This study aimed to determine the relationship between HDL level and blood pressure among patients with hypertension at ODSK Hospital in North Sulawesi Province. This was a retrospective and analytical study using a cross-sectional design. The data used in this study were medical records of all patients with hypertension at the ODSK Hospital in the North Sulawesi Province during the period of April 2022 to September 2023. Samples consisted of patients with hypertension at the ODSK Hospital who meet the inclusion and exclusion criteria. The results showed that the majority patients with hypertension patients with low HDL levels were female (64.9%). Additionally, based on blood pressure the highest percentage of patients with hypertension was in the grade 1 category (57.1%). However, there was no significant correlation between HDL level and blood pressure (both systolic and diastolic) with p-values>0.05 (p=0.683 and p=0.121). In conclusion, there is no significant relationship between HDL level and blood pressure in patients with hypertension at ODSK Regional Hospital, North Sulawesi Province. Keywords: hypertension; blood pressure; high density lipoprotein    Abstrak: Salah satu indikator yang digunakan untuk mengidentifikasi potensi seseorang terkena penyakit hipertensi ialah dengan mengukur profil lipid. Pengukuran kadar kolesterol high-density lipoprotein (HDL) dalam profil lipid berperan penting dalam mengevaluasi risiko hipertensi. Penelitian ini bertujuan untuk mengevaluasi hubungan kadar HDL dengan tekanan darah pada pasien hipertensi di RSUD ODSK Provinsi Sulawesi Utara. Jenis penelitian ialah analitik retrospektif dengan desain potong lintang. Data yang digunakan ialah rekam medik seluruh pasien hipertensi di RSUD ODSK Provinsi Sulawesi Utara pada periode April 2022 – September 2023. Sampel meliputi kelompok kasus pasien hipertensi di RSUD ODSK Provinsi Sulawesi Utara yang memenuhi kriteria inklusi dan eksklusi. Hasil penelitian mendapatkan bahwa berdasarkan kadar HDL, yang terbanyak yaitu kategori kadar HDL pada perempuan <50 mg/dL (64,9%), dan berdasarkan tekanan darah yang terbanyak yaitu kategori derajat 1 (57,1%). Tidak terdapat hubungan bermakna antara kadar HDL dengan tekanan darah sistol dan diastol) pada pasien hipertensi dengan nilai p>0,05 (p=0,683 dan p=0,121). Simpulan penelitian ini ialah tidak terdapat hubungan bermakna antara kadar HDL dengan tekanan darah pada pasien Hipertensi di RSUD ODSK Provinsi Sulawesi Utara. Kata kunci: hipertensi; tekanan darah; high density lipoprotein